Making things : finding use, meaning & satisfaction in crafting everyday objects - Boyle, Erin; Pearlman, Rose (Hardie Grant North America, 2024)
Through easy-to-follow tutorials for over 100 projects that are both accessible and aspirational, Making Things invites readers to try their hands at a variety of crafts and celebrate the satisfaction that comes from slowly and carefully creating for oneself. Learn to fold magazine pages into Masu Boxes for organizing bits and bobs, make a cardboard loom for weaving potholders out of old linens, braid your own Kumihimo Dog Leash, or starch fabric scraps for decorative bunting. Makers Rose Pearlman and Erin Boyle met in 2018 and immediately struck up a friendship, united by a reverence for everyday objects. Their approach towards craft reflects a shared commitment to sustainability and accessibility - as they write in Making Things' introduction, "Craft can be exquisite and exacting, the result of formal training and years of practice, but it can also be experimental and messy and not quite perfect." Scouring sidewalks, stoops, and thrift stores, the authors repurpose materials to create projects that range from functional to fun and frivolous. Step-by-step guides make it simple to start and finish each project, while the book's stunning photographs show how each craft can fit within an organized, thoughtfully curated home. As Making Things demonstrates, relying on a limited range of supplies and repurposing the same materials can spur our creativity, encouraging us to look at a pile of junk on a stoop and see endless possibilities.